Interaction Effects between Doxorubicin and Hernandezine on the Pharmacokinetics by Liquid Chromatography Coupled with Mass Spectrometry - Song, Yang (Molecules, 2019)
Doxorubicin (DOX) is an effective anti-tumor drug widely used in clinics. Hernandezine (HER), isolated from a Chinese medicinal herb, has a selective inhibitory effect on DOX multidrug resistance, making DOX more effective in treating cancer. The aim of this study was to investigate the effect of the interaction of HER and DOX on pharmacokinetics. Male Sparague–Dawley rats were randomly divided into three groups: a single DOX group, a single HER group, and a combination group. Plasma concentrations of DOX and HER were determined by the LC-MS/MS method at specified time points after administration, and the main pharmacokinetic parameters were estimated. The results showed that there were significant differences in the C(max) and AUC(0–∞) of DOX in the single drug group and combined drug group, indicating that HER could improve the absorption of DOX. However, DOX in combination, in turn, reduced the free drug concentration of HER, possibly because DOX enhanced the HER drug–protein binding effect. The results could be used as clinical guidance for DOX and HER to avoid adverse reactions.